Validation of The Canadian Assessment of Physical Literacy - CAPL-2 Questionnaire for German and Polish School Children - Knisel Elke; Bremer Markus; Nałęcz Hanna; Wascher Linus; Laudańska-Krzemińska Ida (Sciendo, 2024)
Physical literacy (PL) is a lifelong process of developing the motivation, confidence, physical competence, knowledge and understanding to value and take responsibility for engaging in physical activity throughout life. It is also an important concept for understanding and promoting physical activity in children and adolescents and is becoming a theoretical basis for analysing physical education in schools. One of the best known, well-operationalised assessments of PL is the Canadian Assessment of Physical Literacy - CAPL-2. The aim of the study was to translate and culturally adapt the CAPL-2 questionnaires in two EU languages, German and Polish. Data from Poland and Germany were combined for this study, with a total sample size of N=802, consisting of 58.6% Polish and 41.4% German students. We used the TRAPD (the Translation, Review, Adjudication, Pre-test and Documentation) approach to translate the CAPL-2 questionnaires. The main results of this study show that the proposed Polish and German versions of the CAPL-2 questionnaires are satisfactory for use in research or for teachers to assess PL in physical education. Our results also indicate better predictive characteristics of the CAPL-2 questionnaires for children who are very close to or who meet the moderate-to-vigorous physical activity (MVPA) recommendations for health as defined by the WHO. We recommend that adaptations be made that are consistent with the original Canadian version, but which are deeply embedded in the language and culture of the country in question, especially in their wording and terminology.